The Biggest Grower - A youth gardening competition for growing specialty crops and urban farmers - Stacy A Adams; Terri James (Urban Food Systems Symposium, 2022)
Youth today have tendencies for unhealthy lifestyles, being sedentary, consuming high fat diets low in fruits and vegetables, all contributing to child obesity, type 2 diabetes, hypertension, and precedence for life-long health concerns. School lunch programs provide opportunity for youth to consume balanced diets but does not make a significant change in lifestyle. Research has identified that youth participating in gardening at home were positively impacted with making lasting healthy choices by improved knowledge and garden connection. For rural and economically disadvantaged urban households, poor diet is directly attributed to the inaccessibility of fresh produce, affordability and understanding of preparation of various specialty crops. Through a grant from the NE Specialty Crop Block Funding Program, The Biggest Grower Competition (BGC) was developed as a summer extension education program for youth in 8th through 12th grade. Project goals included; provide educational materials on gardening, benefits of consuming fresh edibles, and entrepreneurship opportunities; to have participants grow their own crops, collect productivity data, record method of distribution; and, measure behavioral changes in consumption of specialty crops for individual and family. Programs were completed at participants individually during the period of June 1 – August 12 in each of 2020 and 2021. Each developed their own 8 m2 garden (or container collection) and participated in 10 weekly asynchronous virtual educational modules (1 hour per week) and routine synchronous virtual meetings with their Garden Mentor. Participants were invited to come to the University of Nebraska-Lincoln campus (2021) on week 4 for a one-day, no cost program with engagement activities, garden tours, exploration of agriculture technology, and to network with agriculture specialists. Incentives for participation included receiving a multi-action gardening tool, educational book, assorted seeds, colorful logo stickers, and an official contestant t-shirt. Records were maintained of harvest poundage and distribution method. The top eight producers received gift cards in varying amounts as an incentive for ongoing participation and complete submission of data. In 2020, there were 44 participants in which 57% were new to gardening and, for 2021, 17 participants in which 25% were new gardeners. Yearly individual garden production averages were 21.55 kg and 23.13 kg respectively with a total of 1,118.56 kg of fresh produce grown. Through a post-experience survey, daily produce consumption rate increased from 12.5% to 36.4%, 72% of the participants tried a new vegetable/fruit recipe, 91% indicated produce grown was consumed by family, and 18% was donated to food banks.
Keywords: community garden; dietary habits; food security; STEM education; vegetables